DESIGNING A NATIVE PATTERN FOR IMPLEMENTING REFORM POLICIES IN THE ADMINISTRATIVE SYSTEM OF THE ISLAMIC REPUBLIC OF IRAN (Revista Inclusiones, 2019)
Policy development in the administrative system, which can be considered as the government efforts for effective ruling, is one of the major areas of political science and public administration. The purpose of the present study was to design a native pattern for the implementation of the policy of development in the administrative system of the Islamic Republic of Iran. The present study was an applied mixed-method descriptive-correlation study. A questionnaire was designed for this purpose using 19 variables identified in the literature and experts opinion. The sample was 400 managers of superior, middle and lower levels in government departments of Golestan province using a disproportionate stratified sampling method. The results showed that 19 variables were identified in three components: content, structure and Field. The results of path analysis indicated that structural factors were related to implementation of the policy of development in the administrative system, but content and field factors were not related. Development of each country is closely linked to its administrative system and its effectiveness and, in essence, model of development which is followed by the administrative system. Therefore, suggestions were made to create a suitable platform for implementation of the future development policy.